Pengembangan Model Spasial Kebutuhan Air Domestik pada DAS Cisadane Hulu (Batubeulah) - Nisa, Tazkia Nabila; Hidayat, Dina P. A; Andajani, Sih; Kurniyaningrum, Endah; Sejati, Wahyu (Sekolah Tinggi Teknologi Pekanbaru, 2025)
The Upper Cisadane watershed is a strategic area, having an important role in meeting domestic water needs along with population growth and regional development. This study aims to provide an overview of the distribution of domestic water demand by calculating based on district boundaries, watersheds, and built-up areas. The analysis includes the fulfillment of domestic water needs and mainstay discharge, with projections using the arithmetic method. The domestic water demand in each scenario (Scenario I: 3.875 m3/s, Scenario II: 2.755 m3/s, Scenario III: 0.624 m3/s) is presented. The results showed that water availability in the Batubeulah watershed is still surplus, with a minimum Q90% of 14.4 m3/s and a minimum Q95% of 7.6 m3/s, still sufficient to meet the total domestic water demand in all scenarios. Although the water balance between the mainstay discharge and domestic water demand is currently in the safe category. For the results of the projection analysis of scenarios I and II, it shows an increase every year, due to the specifications of the area used.